PELUANG DAN TANTANGAN PENDIDIKAN KARAKTER DI ERA DIGITAL - Fitri Barokah; Sari, Zalia; Chanifudin (LPPM STAI Muhammadiyah Probolinggo, 2024)
This article aims to discuss opportunities and challenges in implementing character education in the digital era in the context of Islamic education. Analysis carried out through library research methods, this article shows that the digital era offers various positive opportunities for character education, such as wider access to learning resources and the use of more interactive learning methods. However, there are also significant challenges that need to be addressed, including digital ethics, cyber security, cyber bullying, sexting, copyright and plagiarism. To overcome this challenge, educational policy makers must play an active role in the sustainable development of digital character learning. This is important to ensure the implementation of digital learning is effective and beneficial for the formation of student character in the digital era. Character education in the digital era requires a holistic approach that includes the development of digital ethics and technical skills. The active role of policy makers and cooperation of all parties is very important to ensure the effectiveness of character education in a digital context. Although the digital era provides various opportunities to improve character education, there are also significant challenges that must be overcome. Collaborative efforts between educators, policy makers, and society are essential to developing effective character education in the digital era. Successful implementation requires a balance between technology and strong moral values, as well as a commitment to developing a holistic approach that supports student character formation. It is hoped that the results of this research will provide new insights for educators, policy makers and the public in developing and implementing effective character education in the digital era. It is also hoped that this research can become the basis for developing educational policies that are more adaptive to the technological and social changes that are occurring.